Restoring function and esthetics in a patient with amelogenesis imperfecta - Saee Deshpande; R D Parkhedkar; Soumil Sarin (Wolters Kluwer Medknow Publications, 2009)
Amelogenesis Imperfecta (AI) is a group of hereditary defects of enamel, unassociated with any other generalized defects. Al results in poor development or complete absence of the enamel of the teeth caused by improper differentiation of the ameloblasts. This report describes the diagnosis and treatment of a young male patient with AI using contemporary restorative strategies. Initially, the tooth surfaces were treated with a professional cleaning along with conservative restorative treatment. Later, full mouth rehabilitation with metal-ceramic crowns was done. The treatment resulted in improved function, esthetics and self-confidence of the patient.